Impact of defined thermomechanical treatment on the structure and content of dietary fiber and the stability and bioaccessibility of polyphenols of chokeberry (Aronia melanocarpa) pomace. (August 2020) - Schmid, Vera; Steck, Jan; Mayer-Miebach, Esther; Behsnilian, Diana; Briviba, Karlis; Bunzel, Mirko; Karbstein, Heike P.; Emin, M. Azad
Graphical abstract: Highlights: Chokeberry pomace – a promising ingredient in the reformulation of cereal products. Good source of dietary fiber (DF) with the potential to partially substitute starch. No remarkable DF alterations due to extrusion-like thermomechanical treatment. Polyphenols degraded but fully bioaccessible after treatment. Abstract: Dietary fiber is a potential replacement for other ingredients such as starch in reformulated extruded breakfast cereals. Analysis of chokeberry pomace powder revealed a total dietary fiber content of 57.8 ± 2 g/100 g with 76% being insoluble, 20% high molecular soluble and 4% low molecular soluble dietary fiber. The fiber polysaccharide composition was analyzed in detail by using a variety of analytical approaches. Extrusion-like processing conditions were studies in a Closed Cavity Rheometer enabling the application of defined thermal (temperature range 100–160 °C) and mechanical treatments (shear rates between 0.1 s −1 and 50 s −1 ) to chokeberry pomace powder. Application of temperatures up to 140 °C irrespective of the mechanical treatment does not remarkably alter dietary fiber structure or content, but reduces the initial content of total polyphenols by about 40% to a final content of 3.3 ± 0.5 g/100 g including 0.63 ± 0.1 g/100 g of anthocyanins, 0.18 ± 0.02 g/100 g of phenolic acids and 0.090 ± 0.007 g/100 g of flavonols, respectively. The retained polyphenols are fully bioaccessible after in vitro digestion, and antioxidant capacity remains unchanged as compared to the untreated pomace powder. Glucose bioaccessibility remains unaffected, whereas glucose content is reduced. It is concluded that chokeberry pomace powder is a good source of dietary fiber with the potential to partially substitute starch in extruded breakfast cereals.